Technology entrepreneurship start-up for the Katarungang Pambarangay Electronic System (KPES) - San Pedro, Conrado G. Jr (University of the Philippines Diliman - Technology Management Center, 2007)
This project aims to provide a business plan for the technology start-up that shall develop, market and effect a technology transfer and diffusion of the Katarungang Pambarangay Electronic System (KPES), a technology solution for the improvement of the barangay justice system toward a more accessible, expeditious and efficient delivery of justice at the grassroots level. KPES is more than just a software package. It is a business process innovation package that comes with technological tools such as the KPES software, the KPES forms, and the KPES user manual. It also comes with a systematic needs analysis for custom-fitting KPES with the current practices of the client's organization and a user-centric training that is easily understandable by the most ordinary person in the client's organization for better technology transfer and adaptation. The objective of bringing the KPES technology solution to the market is three-pronged : First, to create wealth for the technology start-up and its stakeholders; second, to add value to the existing practise in the administration of justice at the barangays by enabling a more expeditious and efficient delivery of justice to the grassroots; and third, to create a nationwide impact as an effect of a collective view of efficient and accessible justice system at the barangays, thus, making a culture of just society. As part of the implementation of this business plan, a knowledge management (KM) program will be designed and carried out across the organization of the technology start-up. The KM program shall enable the organization to capture and deliver a timely response to the market needs for product/service improvement and/or development of new solutions/innovations. Such innovations/development of new solutions would bring yet another opportunity for the technology start-up and its stakeholders to generate more wealth and to contribute further for the improvement of public services for the benefit of more people at the grassroots level, in particular, and the Philippine society, in general. The opportunity for technology transfer in the barangays and the potential to create wealth in the process have been perceived due to the recent developments in the policies of the government that encourage technology-based solutions to be adapted to the government services and the participation of small and medium enterprises in providing such technological services. Product/service development aimed at the barangays shall be done continuously as there will always be a change in policies and how things are done in the said particular local government unit (LGU) due to the inevitable change in leadership every three to five years as an election of local officials (i.e. Sangguniang Barangay or the Barangay Council) shall be held regularly for the said period as provided for in Republic Act No. 7160, otherwise known as the Local Government Code of 1991. This state of affairs is a very good opportunity for the technology start-up to continue on innovating and creating new technology solutions for the LGU's in response to the ever changing needs of the said market. For the KPES to reach the widest LGU market possible, it needs to be marketed effectively althroughout the nation. A guerilla type of marketing will be employed to avoid unnecessary depletion of the very limited capital of the start-up due to marketing alone. This marketing technique will make use of extremely practical tools to reach the LGU's in the most economical way possible without losing quality and a sense of "personal touch." In the sales and distribution of the KPES, agents and partners from various parts of the nation will be tapped to meet sales targets on time, if not faster than expected. Also, existing information and communications technology (ICT) tools, such as the internet and cell phones, will be utilized to facilitate efficient communication between the company and its agents, partners, customers and all the other stakeholders. In addition to the traditional distribution network, political machineries shall be tested if it will be effective in marketing products/services just as they are with their candidates. This is a bit experimental and worth learning lessons from especially when doing business with the LGUs. KPES was designed and developed using an exploratory methodology and will continue to be improved using such methodology. I think this will be the most effective way to innovate KPES as the needs of the LGU's change as often as its leadership does every election. Such innovations, based on the ever-changing market needs, will allow the long-term existence and continuous growth of the technology start-up until it becomes a successful technology firm serving the needs of the LGU's and contributing to the advancement of public services at the grassroots level. KPES will remain an intellectual property of its designer and developer. It will be licensed to the technology start-up, which will be organized by the said designer/developer himself before the implementation of this business plan. The technology start-up shall further develop, market and bring about technology transfer of KPES to the barangays until the technology has been adapted. To avoid creative manipulation of the KPES intellectual property rights, technology licensing will extensively be employed. Licensing will also minimize capital requirements while maximizing growth due to faster and wider technology diffusion through partner-licensees. To ensure the efficient delivery of the objectives of this business plan, competent individuals who are experts in the respective fields of finance, marketing and technology has been carefully chosen to perform key roles in the organization that will run the technology start-up. An income-sharing scheme, in addition to leave credits and allowances, has been crafted to keep the key people on doing their best for the organization. On the other hand, a performance-based compensation package has been designed to keep the other staff, agents and partners on performing at their peak in contributing for the development of the organization. For better resource mobilization, various sources of funding will be considered including those from private investors and those offered by the government. Income-sharing schemes will be constantly employed to encourage individuals and organizations to be agents and partners, respectively, which could spur growth more rapidly despite small initial capitalization. To allow setting of realistic goals, I have been conservative in making market estimates and projections to make room for future improvements. To minimize uncertainties or at least to learn from experience, estimates and projections, as well as the pricing and marketing strategies will be reviewed and revised, if needed, every three months. This practise will also allow the business to react on time to what the market wants and what it needs, including their suggestions for product/service improvement and/or new product/service development. These technological innovations and new product/service development could open doors to yet another wealth-generating business activity that could benefit the company and its stakeholders, the barangays and its constituents, the public and the nation in general.